2021
DOI: 10.1186/s13643-020-01554-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vitamin C supplementation as an adjunct in the non-surgical management of periodontitis: a systematic review

Abstract: Background and objective The antioxidant potential of vitamin C is useful in reducing oxidative stress, free radicals, and reactive oxygen species, which may assist in the improved outcomes of periodontal therapy. This systematic review was aimed to evaluate the effectiveness of vitamin C supplementation as an adjunct to non-surgical periodontal therapy, in the management of periodontitis. Data sources PubMed, EMBASE, Cochrane Library, and Web of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In articles related to periodontitis, the possible effect of dietary VC intake has long been noted and researched [ 5 , 22 ]. Studies have pointed out that people with low VC intake are more prone to periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In articles related to periodontitis, the possible effect of dietary VC intake has long been noted and researched [ 5 , 22 ]. Studies have pointed out that people with low VC intake are more prone to periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to mechanical removal of plaque and other related operations during the treatment process, drugs and diet should also be taken to continuously treat the patient's later oral problems. Vitamin C (VC) in the diet occupies a very important place, and many studies have proved that the physiological role of vitamin C can prevent or treat people suffering from periodontitis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the need for vitamin C increases during intense physical activities [7,8] and in children regularly exposed to cigarette smoke [9,10]. Vitamin C is also recommended in pregnancy and lactation [11], during the growth period of children [12], in diseases such as periodontitis, gingivitis, stomatitis, fractures, osteoporosis [13]. It is also supplemented in haemorrhage due to capillary fragility [14], iron deficiency anaemia (with iron or folic acid), overwork, neurasthenia, prolonged physical effort, serious illness, surgical interventions [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin C is a water‐soluble vitamin with positive effects since it can help to prevent gum disease and gingivitis. Several studies found a positive correlation between vitamin C and periodontitis 46‐48 . The findings suggested that the ascorbic acid assumed regularly with the diet is transferred to the gums through the microcirculation.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies found a positive correlation between vitamin C and periodontitis. [46][47][48] The findings suggested that the ascorbic acid assumed regularly with the diet is transferred to the gums through the microcirculation. According to Tada et al, 46 an improvement in periodontal indices has been demonstrated thanks to an antioxidative effect, a cytotoxic action on bacterial growth, that is Porphyromonas gingivalis and the enhancement of the immune system.…”
Section: Ta B L E 1 Comparison Of the Measurements By Treatmentsmentioning
confidence: 96%